Three-point bending deflection and failure mechanism map of sandwich beams with second-order hierarchical corrugated truss core. (January 2017) - Li, Gang; Fang, Yaochu; Hao, Peng; Li, Zhaokai
For sandwich beams with second-order hierarchical corrugated truss core under three-point bending, a correction factor of shear deflection was firstly proposed to improve the prediction accuracy of the bending analysis, which was verified by finite element analysis and compared with the original formula. Then, the failure modes of the sandwich beam under bending were analyzed, including four competing modes of the large struts (i.e. plastic yielding, buckling, wrinkling of facesheet, shear buckling) and two competing modes of the small struts (i.e. plastic yielding, buckling). Subsequently, the analytical expressions of critical load for each failure mode were derived. On this basis, the failure mechanism maps were constructed. Finally, several typical points from the map were selected and verified by finite element analysis, and a good agreement of predicted failure modes was observed.